Global motion perception is related to motor function in 4.5-year-old children born at risk of abnormal development. (June 2017) - Chakraborty, Arijit; Anstice, Nicola S.; Jacobs, Robert J.; Paudel, Nabin; LaGasse, Linda L.; Lester, Barry M.; McKinlay, Christopher J.D.; Harding, Jane E.; Wouldes, Trecia A.; Thompson, Benjamin; ,
Highlights: Global motion perception is modestly associated with motor development. Stereoacuity is also associated with both gross and fine motor control. Visual acuity was not associated with fine or gross motor control. Abstract: Global motion perception is often used as an index of dorsal visual stream function in neurodevelopmental studies. However, the relationship between global motion perception and visuomotor control, a primary function of the dorsal stream, is unclear. We measured global motion perception (motion coherence threshold; MCT) and performance on standardized measures of motor function in 606 4.5-year-old children born at risk of abnormal neurodevelopment. Visual acuity, stereoacuity and verbal IQ were also assessed. After adjustment for verbal IQ or both visual acuity and stereoacuity, MCT was modestly, but significantly, associated with all components of motor function with the exception of fine motor scores. In a separate analysis, stereoacuity, but not visual acuity, was significantly associated with both gross and fine motor scores. These results indicate that the development of motion perception and stereoacuity are associated with motor function in pre-school children.